United States Patent Law (Open textbook library., 2014)
This Intellectual Property Supplement from eLangdell Press contains the text of federal laws and regulations in the area of copyright, trademarks and patents. The editors have endeavored to gather all relevant laws, rules and regulations. This collection is intended to be used primarily as a statutory supplement for law students and legal scholars in academic settings, although practitioners in this area of law will also find it useful. This volume, Volume 2: Patent Statutory Law contains the text of Title 35 of the United States Code as it appears on the most current edition available on the U.S. Government website FDSYS. Updates to the U.S. Code not yet found in the FDSYS published editions can be found in the United States House of Representatives Office of Law Revision Counsel's Classification Tables. Some formatting modification has been performed to better accommodate electronic readers.